2022
DOI: 10.1039/d2ra02456j
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Zr top electrode on tantalum oxide-based electrochemical metallization resistive switching memory: towards synaptic functionalities

Abstract: Zr is a potential active electrode in the electrochemical metallization cells (ECMs) for the next generation of nonvolatile nanoelectronics. The ECM device works under AC pulses to emulate the essential characteristics of an artificial synapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Figure 5 shows the effect of memristor size on resistive switching in ZnO films. A feature of this approach (prototype 1 in Materials and Methods) is that we can localize resistive switching quite precisely, unlike other approaches, where there is a breakdown problem across the entire top contact due to its massive dimensions [ 41 , 42 , 50 , 51 , 59 ]. Therefore, we can land an AFM probe in any area of the top contact ( Figure 5 a) and ensure that resistive switching occurs at a single location.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows the effect of memristor size on resistive switching in ZnO films. A feature of this approach (prototype 1 in Materials and Methods) is that we can localize resistive switching quite precisely, unlike other approaches, where there is a breakdown problem across the entire top contact due to its massive dimensions [ 41 , 42 , 50 , 51 , 59 ]. Therefore, we can land an AFM probe in any area of the top contact ( Figure 5 a) and ensure that resistive switching occurs at a single location.…”
Section: Resultsmentioning
confidence: 99%
“…The biological brain supports various intellectual functions such as memory, learning, and decision-making [ 37 , 38 , 39 , 40 ]. One of the main ways of technical implementation of the biological brain is to manufacture ICs based on memristor structures, which are memory elements in the form of transition metal oxide film cells (neurons) that change their electrical resistance (between low-resistance (LRS) and high-resistance (HRS) states) under the action of an external electric field, connected by cross-synapses of data [ 41 , 42 , 43 , 44 , 45 , 46 ]. In doing so, ReRAM has a small cell size of a few nanometers, high integration density, high performance, and low power consumption, allowing it to mimic massive parallelism and low-power computing previously seen in the human brain [ 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with the recent rise of quantum applications, the use of resistive Many attempts have been studied to investigate the potential mechanism of doping and, thus, to pursue better performance including voltages, stability, multi-states storage capability as well as synaptic behavior. [24][25][26][27][28][29][30] Lübben et al systematically studied how the material purity, chemistry, and concentrations of intrinsic/extrinsic doping influence devices' kinetics and, thus, affect the performance and functionalities. [24] Raeis-Hosseini et al introduced Zr in TaO x -based RRAM to achieve stable bipolar resistive switching properties with reliable endurance and retention, since the doped Zr can enhance the stability of the conductive filament.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] Raeis‐Hosseini et al introduced Zr in TaO x ‐based RRAM to achieve stable bipolar resistive switching properties with reliable endurance and retention, since the doped Zr can enhance the stability of the conductive filament. [ 25 ] Zhao et al doped Li into SiO 2 by co‐sputtering to form a Li x SiO y ‐based RRAM so that fast programming speed (<10 ns) and reliable endurance(10 9 cycles) were demonstrated. [ 26 ] Ismail et al demonstrated HfAlO x alloy‐based memristor by using ALD to prepare the RS layer, achieving a forming‐free switching behavior with a high current ON/OFF ratio, highly controllable conductance, [ 27 ] and better synaptic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…12 It has two terminal sandwiched structures, which are deemed promising next-generation memory and logic system candidates. 10,13,14 In such sophisticated bionic electronic systems, RRAM is still crucial to achieving low energy consumption, high computing power, and ultrahigh storage density. 15,16 To date, various resistive switching-based synaptic devices built using different materials and bilayer structures have been studied.…”
Section: Introductionmentioning
confidence: 99%